2023
DOI: 10.3390/ijms24065802
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of BCL2 Resistance Mutations in a Real-World Cohort of Patients with Relapsed/Refractory Chronic Lymphocytic Leukemia Treated with Venetoclax

Abstract: The oral, highly selective Bcl2 inhibitor venetoclax has substantially improved the therapeutic landscape of chronic lymphocytic leukemia (CLL). Despite the remarkable response rates in patients with relapsed/refractory (R/R) disease, acquired resistance is the leading cause of treatment failure, with somatic BCL2 mutations being the predominant genetic drivers underpinning venetoclax resistance. To assess the correlation between disease progression and the most common BCL2 mutations G101V and D103Y, sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Thus, based on this study's findings, we consider it probable that during venetoclax treatment of patients, the highly divided CLL cells with the greatest capacity for generating AIDCA-driven mutations will preferentially survive. Once these actively cycling cells later revert to relatively quiescent circulating cells with upregulated BCL2 [72,73], analogously to the transition of germinal center B cells into memory cells [74], any clonal variants with functional BCL2 gene mutations that impair venetoclax binding to BCL2 [14,75] will be venetoclax resistant and could eventually become the dominant CLL subclone [30,70,71]. This hypothesis is consistent with evidence that BCL2 mutations in CLL clonal populations occur prior to treatment and are acquired during treatment [14,15,18].…”
Section: Discussionsupporting
confidence: 61%
“…Thus, based on this study's findings, we consider it probable that during venetoclax treatment of patients, the highly divided CLL cells with the greatest capacity for generating AIDCA-driven mutations will preferentially survive. Once these actively cycling cells later revert to relatively quiescent circulating cells with upregulated BCL2 [72,73], analogously to the transition of germinal center B cells into memory cells [74], any clonal variants with functional BCL2 gene mutations that impair venetoclax binding to BCL2 [14,75] will be venetoclax resistant and could eventually become the dominant CLL subclone [30,70,71]. This hypothesis is consistent with evidence that BCL2 mutations in CLL clonal populations occur prior to treatment and are acquired during treatment [14,15,18].…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, BCL-2 family proteins may undergo posttranslational modifications, including phosphorylation, which alter their activity and may influence mitochondrial apoptosis. 39 Importantly, in the study performed by Guieze et al, 37 patients refractory to venetoclax had detected growing subclones of CLL cells with an amplified region on chromosome 1q23. 40 This region encodes MCL-1 protein and PRKAB2 with the regulatory subunit of AMP-activated protein kinase (AMPK) genes.…”
Section: Chronic Lymphocytic Leukemia/small Lymphocytic Lymphomamentioning
confidence: 99%
“…22,23,35,36 A study performed outside clinical trials revealed that Gly101Val and/or Asp103Tyr mutations were present in 16.7% of patients treated with venetoclax as monotherapy or combined with rituximab. 37 Ninety percent of them further relapsed (median time of follow-up of 26 months (7-32 months)). 37 All of the changes were detected using standard-of-care droplet digital polymerase chain reaction (ddPCR) tests.…”
Section: Chronic Lymphocytic Leukemia/small Lymphocytic Lymphomamentioning
confidence: 99%
See 2 more Smart Citations